Análisis financiero al Gobierno Autónomo Descentralizado Parroquial Rural de La Canela, cantón Palanda, provincia de Zamora Chinchipe, periodos 2021 – 2022 - Guayanay Abad, Janeth (2024)
Financial analysis is an essential tool for assessing the economic and financial situation of institutions. It examines financial statements in detail to identify areas for improvement, make informed decisions, and anticipate possible future situations. Therefore, the objective of this study is to conduct a financial analysis of the Decentralized Autonomous Government of the La Canela rural region, located in Palanda, Zamora Chinchipe province, for the period of 2021–2022, to determine the financial condition of this entity. The study used a quantitative methodology through vertical and horizontal analysis of the GAD's financial statements. Additionally, specific indicators were applied to evaluate the efficiency in resource management and support informed decision-making. The results from the vertical and horizontal analysis revealed significant variations in assets, liabilities, equity, income, and expenses between the years 2021 and 2022. The financial indicators, such as liquidity and solvency, highlighted areas needing improvement to optimize the financial management of the GAD. In conclusion, the financial analysis of the GAD underscored the need to adopt corrective measures to enhance transparency and efficiency in the administration of public funds.